KOMUNIKASI DAKWAH: Interaksi Dan Integrasi Media Sosial - Suharto Suharto (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2013)
Communication media is a media that has mastered the global world. Various forms of media designed to facilitate communication including social media such as twitter, facebook, mailing lists and other. In the context of da'wah communication, social media is very possible for the use of propaganda. Interact through social media to do da'wah or sosialization Islamic teachings and even the integration of social media in communication becomes very important mission for the ease of public access to information about Islam, to motivate people to learn more in-depth and form image of Islam or to counter-information the insult and understimate Islam.